Dentists’ perceived stress and its relation to perceptions about anxious patients - Moore R, Brødsgaard I (Blackwell Synergy, 2001)
Dentists’ perceptions about the stressfulness of dental practice, their perceptions about dental anxiety and its management were surveyed in a descriptive study. A mailed questionnaire was completed by 216 randomly selected Danish private dentists. Of these, nearly 60% perceived dentistry as more stressful than other professions. Dentist perceptions of the most intense stressors were (ranked): 1) running behind schedule, 2) causing pain, 3) heavy work load, 4) late patients and 5) anxious patients.